Probiotic based diets for freshwater prawn Macrobrachium rosenbergii (de Man) - Gupta, Akhil; Dhawan, Asha (Indian Journal of Fisheries, 2013)
Experimental trials were conducted to investigate the impact of incorporation of commercial probiotics viz, â€œlmprovalâ€ and â€œProsolâ€, in supplementary diets of Macrobrachium rosenbergii post-larvae and juveniles. The experiment was conducted in tanks of 350 l capacity for 105 days (60 days for post-larvae and 45 days for juveniles). For each dietary treatment, triplicates were maintained. Ten experimental diets were formulated with different levels of probiotics. In prawns fed with diet containing 4% Improval and 2-3% of probiotic Prosol, significantly higher (p